A systematic review of clinical and diagnostic findings, treatment, and outcomes in canine neosporosis cases evaluated by magnetic resonance imaging - Alisauskaite, Neringa (Frontiers in Veterinary Science, 2025)
BackgroundWhile magnetic resonance imaging (MRI) is increasingly used in the diagnostic workup of canine central nervous system (CNS) disorders, its role in neosporosis has not been systematically characterised. Numerous questions remain regarding optimal diagnostic approaches and treatment protocols, and large-scale studies are lacking.ObjectivesThe objective of the study was to systematically review and analyse published cases of canine neosporosis undergoing MRI examination of the CNS and identify clinical, diagnostic, and treatment variables associated with outcomes.MethodsA comprehensive literature search was performed using PubMed and Google Scholar. The inclusion criteria were confirmation of N. caninum infection by serology, polymerase chain reaction (PCR), or histopathology, and MRI performed at diagnosis. Extracted data included signalment, clinical signs, MRI features, cerebrospinal fluid (CSF) results, serology, PCR, treatment, and outcomes. Statistical analyses assessed associations and correlations among diagnostic and outcome variables.ResultsEighty-two cases extracted from 11 publications met the inclusion criteria. MRI commonly revealed multifocal intra-axial lesions, frequently involving the cerebellum, with variable contrast enhancement of the brain and spinal cord and meninges, and consistent contrast enhancement in the muscles. A significant association was identified between elevated cerebrospinal fluid total nucleated cell count (CSF TNCC) and positive cerebrospinal fluid polymerase chain reaction (CSF PCR). Treatment duration strongly correlated with survival. Death/euthanasia due to neosporosis occurred in one-third of the cases. Remissions were rare. Relapses occurred despite initial improvement.ConclusionCanine neosporosis presents with diverse neurological clinical signs and MRI features. The disease mainly affects young-to-middle-aged adults with multifocal CNS involvement, and CSF is abnormal in the majority of cases. Review analyses showed that serology titres, serum creatine kinase (CK) levels, CSF TNCC, CSF PCR results, and MRI contrast had no prognostic value, while higher CSF TNCC was associated with positive CSF PCR. The only consistent prognostic marker was treatment duration—longer antimicrobial therapy was correlated with improved survival. Although the prognosis remains guarded, early recognition and prolonged antimicrobial treatment are key to improving outcomes.